How Integrated Is SADC? Trends in Intra-Regional and Extra-Regional Trade Flows and Policy - Behar, Alberto; Edwards, Lawrence (2012)
Do Southern African Development Community countries trade enough with each other and with the rest of the world? Although its share of world trade has fallen, appropriate benchmarking shows that, controlling for gross domestic product and other characteristics, Southern African Development Community countries have experienced an increase in openness that is comparable to other developing countries. Once market size and geography are taken into account, trade between Southern African Development Community countries is actually high. Southern African Development Community countries also trade more products with each other than they do with the rest of the world. In this sense, and contrary to stylized fears, the Southern African Development Community region is quite integrated. Although the Southern African Development Community has reduced its tariffs, the structure remains complex and could be lowered on intermediates. Other impediments make it costly and difficult to move goods, but are at levels that are comparable with countries at similar levels of development. Although this may be surprising, there is still scope for improvement and the disadvantageous geography of the Southern African Development Community makes it important for other trade impediments to be reduced.